Using Outage History to Exclude High‐Risk Satellites from GBAS Corrections. Issue 1 (27th November 2012) - Pullen, Sam; Enge, Per
ABSTRACT GNSS augmentation systems that provide integrity guarantees to users typically assume that all GNSS satellites have the same failure probability. The assumed failure probability is conservative such that variations among satellites in a given GNSS constellation are not expected to violate this assumption. A study of unscheduled GPS satellite outages from 1999 to 2011 shows that, as expected, older satellites are much more likely to fail than younger ones. In addition, satellites that have recently experienced unscheduled outages are more likely to suffer additional unscheduled outages. Combining these two factors suggests that it is possible for a subset of GPS satellites to violate the overall satellite failure probability assumption, although this has not yet been demonstrated. Potential rules for GPS satellite exclusion based upon satellite age and recent outages are investigated, and suggestions for including satellite geometry are explored. Copyright © 2012 Institute of Navigation.